The role of oxidative stress in modulating mortality risk across the hypertension control cascade - Liu, Weihao; Hou, Chunyang; Wang, Hongjie; Du, Hao; Dai, Xianyu; Jiang, Yu; Hou, Yuchuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe role of oxidative stress in hypertensive populations has not yet been fully elucidated. This study examines the association between the Oxidative Balance Score (OBS) and all-cause and cardiovascular mortality under different hypertension control cascade outcomes while assessing mediation by low-grade systemic inflammation and multi-organ function.MethodsThis cohort study analyzed 1999–2018 NHANES data, with mortality outcomes from the National Death Index (NDI). It encompassed U.S. adults with hypertension. OBS consists of 20 nutrition and lifestyle factors. Low-grade systemic inflammation (NLR, SIRI) and multi-organ function (eGFR, UACR, FIB-4 index, SUA) were examined as potential mediators. Statistical analyses included Kaplan–Meier analysis, Cox models, restricted cubic splines (RCS), subgroup analyses, and mediation analysis.ResultsParticipants in the highest OBS quartile (Q4) exhibited lower all-cause mortality (HR: 0.72; 95% CI: 0.59–0.88; P = 0.001) and cardiovascular mortality (HR: 0.64; 95% CI: 0.42–0.99; P = 0.044) than Q1 after adjusting for confounders. The OBS-mortality association varied by hypertension control status, with greater risk reduction in controlled hypertension (Q4 vs. Q1, HR: 0.43; 95% CI: 0.27–0.69; P < 0.001) than in uncontrolled hypertension (Q4 vs. Q1, HR: 0.82; 95% CI: 0.66–0.87; P < 0.001). A significant interaction was observed between OBS and hypertension control status (P for interaction = 0.017 and 0.026), corroborated by sensitivity analyses (P for interaction = 0.025). Sensitivity analyses confirmed Nutrition-OBS reduced all-cause mortality by 31%, and Lifestyle-OBS decreased cardiovascular mortality by 45%. RCS analyses verified the inverse OBS-mortality relationship, with mediation analysis revealing partial mediation through low-grade systemic inflammation and multi-organ function.ConclusionsA higher OBS is associated with lower all-cause and cardiovascular mortality under different hypertension control cascade outcomes, with a more pronounced effect in controlled hypertension. This relationship is partially mediated through systemic inflammation and multi-organ function.